Foucault's contributions for understanding power relations in British classical political economy - Danielle Guizzo (EconomiA, 2015)
This paper analyzes the strategic role played by British classical political economy in constructing new technologies of power. Michel Foucault drew attention to a change that political economists promoted concerning the role of the state, which has been overlooked by historians of economic thought. This paper explores the main arguments provided by the most important British political economists of the 18th and 19th centuries on what concerns population management, State's role and economic dynamics in order to examine Foucault's considerations. Although British classical political economy consolidated the mechanism of markets and economic individuality, thus creating a system of truth that changed economic norms and practices, its discourse also established a political conduct that was responsible for creating mechanisms of control that disseminated new forms of power relations. – – Este artigo analisa o papel estratégico desempenhado pela economia política clássica britânica na construç\~ao de novas tecnologias de poder. Michel Foucault chamou a atenç\~ao para uma mudança promovida por economistas políticos com relaç\~ao ao papel do Estado, fato que foi ignorado por historiadores do pensamento econômico. Este artigo explora os principais argumentos fornecidos pelos principais economistas políticos britânicos dos séculos XVIII e XIX no que diz respeito à administraç\~ao da populaç\~ao, ao papel do Estado e a dinâmica da economia a fim de examinar as consideraç\~oes de Foucault. Apesar de a economia política britânica ter consolidado o mecanismo dos mercados e o individualidade na esfera econômica, criando assim um sistema de verdade que modificou as normas e práticas econômicas, seu discurso também estabeleceu uma conduta política responsável por criar mecanismos de controle que disseminaram novas formas de relaç\~oes de poder.
Keywords: A12; B12; 330; British classical political economy; Genealogy of power; Liberal art of government; Biopolitics